Adsorption of Silanediol-Like Molecules on tio2 Nano-Clusters: A Density-Functional-Theoretic Study - Escrig-Murua, J (Elsevier Ltd, 2023)
We performed density-functional-theoretical calculations of the silanediol-like molecules adsorbed on (TiO2)20 tetrahedral-like clusters. We study the adsorption on the triangular face of the (TiO2)20 clusters in two different sites (Center and Edge). Our results suggest that the band gap of the (TiO2)20 nano-clusters can be controlled (tune or adjust) changing the length of the molecule as well as the terminal element within the molecule chain. The adsorption energy or functionalization energy of the cluster is almost independent of the number of atoms, presenting only a slight increase with the number of atoms in the adsorbed molecular chain. We also analyze the dependence of the gap with iso-electronic final monomer for a few selected cases. © 2023 Elsevier Ltd